Technical and Economical Assessment of Biomass Potential for Power Production: A Study in the South of Italy - Messineo, Antonio; Bonasera, Davide; Volpe, Roberto; Messineo, Simona; Marvuglia, Antonino (Journal of Environmental Accounting and Management, 2026)
The use of biomass, among the various forms of renewable energy, has assumed a key role in the current European Union agenda. In 2005 the European Commission launched a “biomass action plan” in order to promote the development of biomass energy from wood, waste and agricultural crops and stimulate economic activities in rural areas. Among the various types of biomass, agroforestry residues are the prevalent amount in the country and the most readily available. However their use, in the production of electricity or in a cogeneration form, has not taken off for small plants. The main problems are related to the local availability of the resource, to logistics problems, to the purchase price and to the reliability of conversion technologies. This paper aims to analyze the residual agroforestry biomass (herbaceous and woody) in the administrative province of the city of Enna (Italy) and to evaluate the financial viability of a small gasification plant (